Bilan 2005 du réseau REPAMO - Réseau national de surveillance zoosanitaire des mollusques marins - Garcia, Celine; Arzul, Isabelle; Chollet, Bruno; Ferrand, Sylvie; Francois, Cyrille; Joly, Jean-pierre; Miossec, Laurence; Robert, Maeva; Cuvelier, Nicolas; Lefebvre, Alain; Le Gagneur, Eric; Ropert, Michel; et al. (2006)
Created in 1992, the REPAMO network (Network of mollusc pathology), is a national zoosanitary surveillance network of shellfish health status along the French coasts. Ils activities are in keeping with two European Directives, 91167/EEC and 95170/EC and are a part of the institutional tasks of Ifremer. The aims of the network are to prevent the introduction and spread of exotic pathogens and to sm'vey the evolution of notifiable pathogens already present in France. The network focused on the survey of listed diseases (bonamiosis and marteiliosis of flat oyster) in two areas under agreement process (Granville bed and zone X). In 2005, only samples of the Granville bed could be analysed due to the difflculty to obtain flat oysters (sparse oyster beds, beds no easy accessible). The notifiable parasite Bonamia ostreae was observed in two oysters of Granville bed; an inquiry was conducted and it revealed that oysters came from an area outside of the wild bed. In 2005, the study of abnormal mortalities has been carried on and the number of reported cases was lower than 2004. Mortality occurred mostly in summer and affected the main production areas. Majority reports concemed Pacific oyster, Crassostrea gigas. OsHV-1 was detected in several mortality cases of oyster spat like previous years. The notifiable parasite Haplosporidium nelsoni was frequentiy observed in 2005 but the detection frequency remains low (<1%). Several abalone mortalities were recorded in abalone beds of Normandy; Vibrio harveyi seems to be involved in these mortalities. Some pathogens were detected associated with mortality cases but ail the mortality cases could not be explained by pathogens. Environmental, physiological, zootechnical factors could play a direct or indirect part in reported mortalities. In 2004-2005, the zoosanitary surveillance of cultured and wild populations of shellfish concerned the clams Ruditapes decussatus and R. philippinarum particularly their infection by the parasite Perkinsus olseni. 9 areas were sampled in 2005 ...